Committed Effective Doses Received by Occupational Workers Handling Radioisotopes (131I and 99mTc) at INMAS, as Assessed from Urine-Samples (Dhaka University Journal of Science, 2020)
This study estimates the potential health risks attributed to the internal contamination of occupational workers at the Institute of Nuclear Medicine and Allied Sciences (INMAS) located at Dhaka Medical College and Hospital, Dhaka, during nuclear medicine practices involving the radionuclides 131I and 99mTc, using in vitro methods from urine samples. A total of 55 urine samples from 6 occupational workers are collected over a period of about 11 months. These samples are analyzed using a High Purity Germanium (HPGe) detector coupled with a multichannel analyzer (MCA). The radioactivity of the isotopes present in each urine sample is measured based on the detector efficiency, and the committed effective dose due to each intake is calculated from this activity. The average annual doses of individual workers found in this study range from 4.57 × 10-5 mSv to 9.72 × 10-3 mSv. Although these doses are considerably below the International Commission on Radiological Protection (ICRP) recommended annual dose limit of 20 mSv, efforts to abide by the ALARA principle should continue.Dhaka Univ. J. Sci. 68(2): 161-165, 2020 (July)